Carta de Vicente Geigel Polanco a Antonio Vélez Alvarado - Geigel Polanco, Vicente; Vélez Alvarado, Antonio (My University, 1937)
Carta relacionada a la bandera puertorriqueña en 1895.
Keywords: Bandera--Puerto Rico.; Flags--Puerto Rico.